The Composition and Distribution of Financial Assistance From Arab Countries and Arab Regional Institutions. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper examines the volume and distribution of concessional and nonconcessional financial flows from Arab countries, and aid agencies, and regional institutions to developing countries. Arab financial assistance increased very rapidly from 1973 to 1980 in line with the rapid growth in oil revenues. Essentially because of the softer oil market, this trend was reversed in the 1980s. Nonetheless, the Arab contributions as a share of GNPs remain by far the most generous among the major donor groups. Arab recipient countries received nearly 62 percent of total Arab financial assistance. Together with large flows of workers' remittances, this assistance accelerated their economic development beyond what would have been otherwise possible.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet